Women's Participation in Cultural Tourism Based Community Empowerment - Hasdiani, Tanisa; Mulyono, Sungkowo Edy; Abimbowo, Yusuff Olatunji (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2024)
Kampung Batik is one of the cultural tourism destinations and has been the largest Batik producer in Semarang city since the 18th century. Most of the population consists of women who are actively involved in Batik cultural activities. The research aims to describe the stages, the forms, and the impact of women's participation in community empowerment. The study was designed with a descriptive qualitative approach involving three female members, including the Tourism Assistance Community of Kampoeng Djadhoel chairman, the Neighborhood Head of Kampung Batik, and the Kampung Batik community. Data were collected through participatory observation, interviews, and documentation. Data validity testing was carried out using triangulation of sources and techniques. The stages of data analysis were data collection, data reduction, data presentation, and conclusion drawing. The results showed that the stages of women's participation included decision-making, activity implementation, monitoring and evaluation, and utilization of development results. The positive impact of women's participation is increased employment, income, and skills; the negative effect is the problem arising from Batik waste management. This research can be a reference for the government, society, and women to improve women's welfare through empowerment.